Log in to add a comment

## Answers

### This Is a Certified Answer

Certified answers contain reliable, trustworthy information vouched for by a hand-picked team of experts. Brainly has millions of high quality answers, all of them carefully moderated by our most trusted community members, but certified answers are the finest of the finest.

X-y = 4

x = y+4

xy=192

(y+4)y = 192

y² + 4y - 192 = 0

(y-12)(y+16)=0

y =

x =

x = y+4

xy=192

(y+4)y = 192

y² + 4y - 192 = 0

(y-12)(y+16)=0

y =

**12**x =

**16**given that a-b=4 equation 1

and ab=192

according to

(a+b)^2 - (a-b)^2 = 4ab

substitute above values in above formula

then we get

(a+b)^2 - (4)^2 = 4*192

(a+b)^2 - 16 = 768

(a+b)^2 = 768 + 16 = 784

a+b = square root(784)

a+b = 28 equation 2

subtract equation 2 and equation 1

we get 2b= 24

b = 12

then b=18 substitute in equation 2 then a = 28-12 = 16

therefore the two numbers are 16 and 12